Production and composition of buffalo milk supplemented with agro industrial byproducts of the african palm (2017)
The goal for this applied research was to assess the production and composition of buffalo milk when Oil Palm kernel flour and Oil Palm kernel cake are supplemented to their diet. Thirty buffaloes from the grasslands of the Andes valleys in Colombia with 1 to 3 lactations and an average weight of 575 kg were selected for the experimental. The animals were randomly assigned to one of three experimental groups: (T1 Control Group) with no diet supplements, (T2) 1000 g·day-1 of oil palm kernel cake and 350 g·day-1 of molasses diet supplement, and (T3) 1150 g·day-1 of oil palm kernel flour. During the first 100 days of lactation, the milk livestock were individually weighed and milked. Milking was scheduled every 15 days, for a total of seven samples. The supplement consumption was recorded and a bromatological analysis of grasses was performed. The chemical composition of the milk was determined using an ultrasonic Ekomilk analyzer and a fatty acid full profile analysis was made using High Liquid Pressure Chromatography (HLPC). A 7 x 3 multiple variable statistical analysis was performed by sampling seven fifteen day periods and three types of diet. The average values of milk components observed were: 3.54% protein; 7.4% fat; total solids 16.9%; non-fat solids 9.5%; 2.1 fats to protein ratio. The profile of fatty acids showed 2.34% of polyunsaturated; 33.1% of monounsaturated; 64.6% of unsaturated fatty acids; and 0.96% of Omega 6 acids. In conclusion was observed partial effect to fat supplementation in the buffaloes milk production.